POSSÍVEL MARCADOR CITOTAXONÔMICO PARA O GÊNERO DICHOTOMIUS (COLEOPTERA SCARABAEIDAE) - Nascimento, J.M.; Silva, F.A.B.; Moura, R.C.; Rocha, M.F. (Revista Nordestina de Zoologia, 2010)
The genus Dichotomius has more than 154 described species and nine species studied to the cytogenetic level. The aim of this study was to examine through conventional staining the mitotic and meiotic chromosomes of 20 specimens of Dichotomius prox. sericeus collected in Aldeia, municipality of Paudalho, State of Pernambuco. The species studied had the karyotype 2n = 18 + Xyp (meioformula 8II + Xyp) and meta-submetacentric chromosomes. This chromosome number is common among the species analyzed cytogenetically and seems to be a chromosomal marker for Dichotomius. D. prox. sericeus also presented a differential chromosome by display constrictions. The cytogenetic data obtained in this study contributes to the understanding of cytological and evolutive patterns of the genus Dichotomius.